SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KARYAWAN BERPRESTASI BERBASIS WEB DENGAN METODE TOPSIS. (STUDI KASUS: PT. GUMARA TRANS JAYA BOJA) - Rusito, Rusito; Widiyanto, Restu (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
One of the most crucial elements in a company is Human Resources (HR). To ensure a conducive internal climate within the company, creating healthy competition among employees can be achieved by selecting the best candidates. The process of selecting the best employees at PT. Gumara Trans Jaya Boja relies on criteria-based data without accurate calculations. The purpose of this research is to provide a system that can make decisions about high-performing employees using the TOPSIS method and to implement this method in determining the criteria for assessing high-performing employees to ensure accurate data for precise decision-making and optimal results. The system is built using the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution), with XAMPP as its server, PHP as the programming language, and MySQL as the database. The testing results of this decision support system were deemed valid, receiving a score of 3.7, or 'Good', from expert evaluators, and obtaining a score of 4.2, or 'Very Good', from users. In a comparative test, the newly designed system achieved an 84% level of system alignment with the assessment indicators, compared to the old system's 44% alignment. This research follows the 6-step R&D method.